Positive pole piece based on gradient structure as well as preparation method and application of positive pole piece

By adopting a gradient structure design in the positive electrode sheet, the ratio of the positive electrode material, solid electrolyte and conductive carbon black is adjusted layer by layer, and the problem of insufficient conductivity balance of batteries under high loads in the prior art is solved, and high energy density, long life and excellent conductive properties are achieved.

CN119725377AActive Publication Date: 2025-03-28TIANFU JIANGXI LAB
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411914924.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The prior art has shortcomings between balancing high load performance, cycle life and excellent electron and ion conductivity, especially under high load conditions, the ion and electron transport path of the battery is extended, resulting in a decrease in reaction kinetics and the inability to fully exert capacity and power density.

Method used

The positive electrode sheet design based on the gradient structure is adopted, and the ratio of the positive electrode material, solid electrolyte and conductive carbon black is adjusted layer by layer to ensure that the battery's energy density, structural stability and long cycle life are taken into account under high load conditions. The specific design includes the material with a high nickel content on the bottom layer, the material with a gradually reduced nickel content on the intermediate layer that increases the manganese content, and the material with a high manganese content on the surface layer. The proportion of solid electrolytes and conductive agents of each layer of materials varies with the ion and electron transport distance to optimize conductivity.

Benefits of technology

It effectively balances the battery's performance requirements under high load conditions, improves the comprehensive performance of solid-state batteries, significantly extends the battery's service life and cycle stability, and improves the battery's charging and discharging efficiency and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725377A_ABST
    Figure CN119725377A_ABST
Patent Text Reader

Abstract

The invention discloses a gradient structure-based positive pole piece and a preparation method and application thereof, and relates to the technical field of electrochemistry, the positive pole piece comprises a bottom layer, a middle layer and a surface layer; each of the bottom layer, the middle layer and the surface layer comprises a positive electrode active material prepared from transition metal materials in different proportions; the transition metal material comprises Ni, Co and Mn, and from the bottom layer to the surface layer, the content of Ni is gradually reduced, and the content of Mn and Co is gradually increased. By designing the three-layer gradient positive electrode structure, the composition of the positive electrode material is optimized, the energy density of the battery is improved, and the electron and ion conductivity of the battery under high load is improved by reasonably configuring the ratio of the solid electrolyte to the conductive agent, so that the cycling stability and the conventional rate capability of the battery are enhanced; and a plurality of performance requirements of the battery under a high-load condition can be effectively balanced, the comprehensive performance of the solid-state battery is improved, and a feasible technical path is provided for the solid-state lithium battery with high energy density and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a positive electrode sheet based on a gradient structure, and a preparation method and application thereof. Background Art

[0002] With the growing demand for new energy, solid-state batteries, as the next generation of battery technology, have attracted widespread attention due to their high safety, long cycle life and excellent energy density. In the field of solid-state sulfur physical batteries, the performance of the cathode material has an important influence on the overall performance of the battery, especially key parameters such as energy density, cycle life and rate performance. In order to improve the performance of batteries, researchers have adopted a variety of optimization strategies, such as high-load cathodes, ternary cathode materials, and gradient cathode material design. These technologies can effectively improve the conductivity and structural stability of the electrode, especially in batteries with high cathode loads, which can effectively improve the energy density of the battery.

[0003] Although current technology has made some progress in improving the performance of the positive electrode, under high load conditions, the ion and electron transmission paths of the battery will be extended, resulting in a decrease in the battery reaction kinetics, and the battery capacity and power density cannot be fully utilized. Although the structural stability and cycle life of the positive electrode are improved by adjusting the gradient structure design, the contact between the solid electrolyte and the positive electrode material is incomplete under high load, which limits the ion conductivity of the battery. Moreover, although the use of conductive agents can improve electronic conductivity, their uneven distribution or insufficient to meet the needs of high-load batteries leads to a decrease in cycle performance.

[0004] In general, existing technologies still have certain deficiencies in balancing high-load performance, cycle life, and excellent electronic and ionic conductivity. Summary of the invention

[0005] Based on the fact that the current positive electrode sheets still have certain deficiencies in balancing high load performance, cycle life and excellent electronic and ionic conductivity, the purpose of the present invention is to provide a positive electrode sheet based on a gradient structure and its preparation method and application, which can effectively balance multiple performance requirements of the battery under high load conditions, improve the comprehensive performance of solid-state batteries, and provide a feasible technical path for high energy density and long life solid-state lithium batteries.

[0006] The present invention is achieved through the following technical solutions:

[0007] In the first aspect, the present application provides a positive electrode plate based on a gradient structure, comprising a bottom layer, an intermediate layer and a surface layer; the bottom layer, the intermediate layer and the surface layer all comprise positive electrode active materials prepared using transition metal materials in different proportions; the transition metal materials comprise Ni, Co and Mn, and from the bottom layer to the surface layer, the Ni content gradually decreases, and the Mn and Co contents gradually increase.

[0008] The present invention ensures that the energy density, structural stability and long cycle life of the battery can be taken into account under high load conditions by regulating the composition and structure of each layer of positive electrode materials. Specifically, the first layer uses a ternary positive electrode material with a high nickel content to improve the energy density; the second layer serves as a transition layer, with a gradually reduced nickel content and a gradually increased manganese content, thereby improving structural stability; the third layer uses a material with a high manganese content to further improve the battery's oxidation resistance and cycle life. The ratio of solid electrolyte and conductive agent in each layer of material changes with the transmission distance of ions and electrons, ensuring that the ionic conductivity and electronic conductivity between different layers are optimized, thereby enhancing battery performance under high load.

[0009] The present invention not only optimizes the composition of the positive electrode material and improves the energy density of the battery by designing a three-layer gradient positive electrode structure, but also improves the electronic and ionic conductivity of the battery under high load by rationally configuring the ratio of solid electrolyte and conductive agent, thereby enhancing the cycle stability and conventional rate performance of the battery. The three-layer gradient positive electrode structure of the present invention can effectively balance multiple performance requirements of the battery under high load conditions, improve the comprehensive performance of the solid-state battery, and provide a feasible technical path for high energy density and long life solid-state lithium batteries.

[0010] In a specific embodiment, the positive electrode active material of the bottom layer includes Li(Ni 0.83 Co 0.11 Mn 0.06 )O2; the positive electrode active material of the intermediate layer includes Li(Ni 0.6 Co 0.2 Mn 0.2 )O2; the positive electrode active material of the surface layer includes Li(Ni 0.33 Co 0.33 Mn 0.33 )O2.

[0011] In a specific embodiment, the raw material components for preparing the positive electrode plate also include solid electrolyte, conductive carbon black, binder, and solvent.

[0012] In a specific embodiment, the solid electrolyte includes Li6PS5Cl, whose excellent ionic conductivity and good interface stability are helpful to reduce the interface resistance.

[0013] In a specific embodiment, the conductive carbon black includes Super P conductive carbon black. Conductive carbon black can enhance the conductivity of electrons.

[0014] In a specific embodiment, the binder includes polyvinylidene fluoride. The polyvinylidene fluoride binder can ensure stable bonding between the electrode material and the conductive carbon black.

[0015] In a specific embodiment, the solvent includes N,N,N-trimethyl-2-aminoethanol. N,N,N-trimethyl-2-aminoethanol can improve the solubility and dispersibility of the slurry and ensure its uniformity.

[0016] In a specific embodiment, by mass ratio, in the bottom layer, the positive electrode active material: solid electrolyte: conductive carbon black = 70: (20-24): (6-10); in the middle layer, the positive electrode active material: solid electrolyte: conductive carbon black = 70: (24-26): (4-6); in the surface layer, the positive electrode active material: solid electrolyte: conductive carbon black = 70: (18-22): (8-12).

[0017] The positive electrode sheet design of the present invention adopts a gradient structure, and aims to balance the ionic conductivity and electronic conductivity of the battery by optimizing the ratio of positive electrode materials, solid electrolytes and conductive carbon black layer by layer. Considering the characteristics that the transmission paths of ions and electrons change with the layers, the design is further explained as follows:

[0018] Bottom layer (close to the current collector): Since the interface between the current collector and the coating is crucial to the internal resistance and cycle performance, increasing the proportion of conductive carbon black in the bottom layer can effectively reduce the contact resistance of the interface and improve the internal resistance and cycle stability of the battery. At the same time, in order to enhance the ionic conductivity of the bottom layer, the proportion of solid electrolyte is appropriately increased. The design of this layer ensures good ionic and electronic conductivity, especially the performance under high load and rapid discharge.

[0019] Middle layer: As the distance from the current collector increases, the proportion of solid electrolyte increases moderately to maintain sufficient ionic conductivity and support efficient charging and discharging of the battery. In this layer, the proportion of conductive carbon black decreases slightly to gradually transition to a structural configuration more suitable for optimizing electronic conductivity.

[0020] The proportion of solid electrolyte is reduced on the surface layer (the side away from the current collector) and the content of conductive carbon black is significantly increased. The main purpose is to optimize electronic conductivity, reduce internal resistance, and improve the energy release efficiency of the battery. Under this design, the discharge performance of the battery is improved, especially at conventional rates.

[0021] In a second aspect, the present application provides a method for preparing a positive electrode sheet, comprising the following steps:

[0022] Preparation of composite positive electrode material: mixing positive electrode active material, solid electrolyte and conductive carbon black in proportion, then adding binder and solvent to the composite positive electrode powder, and premixing in a vacuum zirconia ball mill;

[0023] Layer by layer coating:

[0024] The first coating layer is to coat the slurry of the bottom cathode material on the aluminum foil;

[0025] The second layer is coated by coating the slurry of the intermediate layer positive electrode material on the surface of the first layer;

[0026] The third layer coating is to coat the slurry of the surface positive electrode material on the surface of the second layer;

[0027] Each layer is dried after coating and heat treated by low temperature annealing.

[0028] In one specific embodiment, the loading amounts of the three layers are the same.

[0029] In one embodiment, the total loading of the three layers is 45 mg / cm 2 .

[0030] In a specific embodiment, the mass ratio of the composite positive electrode powder to the binder is 100:(1-5).

[0031] In a third aspect, the present application provides a battery, comprising the above-mentioned positive electrode plate or the positive electrode plate prepared by the above-mentioned preparation method.

[0032] In a specific embodiment, the method for preparing the battery comprises the following steps:

[0033] Cut the positive electrode sheet into round pieces and place them at the bottom of the mold;

[0034] Evenly spread electrolyte powder or electrolyte film on the positive electrode sheet and compact the electrolyte surface;

[0035] Spreading the graphite composite negative electrode powder evenly on the surface of the electrolyte;

[0036] The entire battery assembly is placed under a stacking pressure of 50MPa to 80MPa for pressing to ensure that each layer of material is tightly bonded to prepare a battery.

[0037] In a fourth aspect, the present application provides an electronic device, which includes the above-mentioned battery. The battery described herein includes a high-performance lithium-ion battery, which can be widely used in electric vehicles, power tools, energy storage systems, portable electronic devices and other fields.

[0038] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0039] (1) The positive electrode plate of the present invention adopts a gradient structure design and adjusts the ratio of positive electrode material, solid electrolyte and conductive carbon black layer by layer, which effectively solves the problem that the positive electrode plate in the prior art is difficult to optimize the ionic conductivity and electronic conductivity of the battery at the same time, that is, solves the problem of insufficient balance between electrical conductivity and ionic conductivity in the prior art.

[0040] (2) The present invention adopts a gradient structure design to place a high nickel content in the bottom layer to improve the energy density, and increases the manganese content in the middle layer and the surface layer to improve the oxidation resistance and stability of the battery material, thereby significantly extending the battery life and cycle stability, and solving the problem of material performance degradation that often occurs in traditional batteries during long-term use, especially under high load conditions.

[0041] (3) The present invention increases the amount of conductive agent in the bottom layer, thereby enhancing the contact between the coating and the current collector, thereby effectively reducing the internal resistance and improving the charge and discharge efficiency of the battery, solving the problem in the prior art that the internal resistance of the battery is high, limiting its performance under high load conditions.

[0042] (4) The present invention optimizes the energy density, conductivity and stability of the battery through the gradient design of the bottom layer, middle layer and surface layer. Under the conditions of high load and long-term use, it shows good comprehensive performance and has strong market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0044] Figure 1 It is a schematic structural diagram of a positive electrode plate based on a gradient structure and its corresponding solid-state battery in the present invention. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0046] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, well-known materials or methods are not specifically described.

[0047] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" that appear in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any appropriate combination and / or sub-combination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items. In addition, those skilled in the art will be able to combine and combine different embodiments or examples described in this specification and features of different embodiments or examples, without contradicting each other.

[0048] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0049] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0050] Example 1

[0051] This embodiment provides a method for preparing a positive electrode sheet based on a gradient structure and a method for preparing a battery using the positive electrode sheet, and the specific steps are as follows:

[0052] S1. Material selection and gradient design

[0053] The bottom layer is made of high nickel content (Li(Ni 0.83 Co 0.11 Mn 0.06 )O2) cathode material, aiming to increase the energy density of the battery; the intermediate layer uses a cathode material with a moderate nickel content and increased manganese content ((Li(Ni 0.6 Co 0.2 Mn 0.2 )O2) to enhance the structural stability of the battery; the surface layer uses a positive electrode material with a high manganese content (Li(Ni 0.33 Co 0.33 Mn 0.33 )O2), improving cycle life and oxidation resistance. The solid electrolyte uses Li6PS5Cl, which has excellent ionic conductivity and good interface stability, which helps to reduce interface resistance. Conductive carbon black uses Super P, which can effectively enhance the electronic conductivity of the electrode. As a binder, polyvinylidene fluoride (PVDF) is used to ensure a good combination of the positive electrode material and the conductive carbon black. In addition, N,N,N-trimethyl-2-aminoethanol (TNMP) is selected as a solvent to improve the solubility and dispersibility of the slurry and ensure its uniformity.

[0054] S2. Gradient structure design and ratio optimization

[0055] According to the design concept of the gradient structure, the ratio of solid electrolyte and conductive carbon black in each layer of positive electrode material is optimized according to the ionic and electronic conductivity requirements of the battery.

[0056] The bottom layer (close to the current collector) is designed as positive electrode active material: solid electrolyte: conductive carbon black = 70:24:6. The proportion of conductive carbon black is increased to effectively reduce the contact resistance at the interface between the current collector and the coating, improve the internal resistance and cycle stability, and enhance the ionic conductivity by appropriately increasing the proportion of solid electrolyte.

[0057] The middle layer (the side away from the current collector) is designed as positive electrode active material: solid electrolyte: conductive carbon black = 70:25:5. The solid electrolyte ratio is moderate, aiming to balance the conductivity of ions and electrons and support efficient charging and discharging of the battery.

[0058] The surface layer (the side away from the current collector) is designed to be positive electrode active material: solid electrolyte: conductive carbon black = 70:20:10, reducing the proportion of solid electrolyte, significantly increasing the content of conductive carbon black, and optimizing electronic conductivity to meet high load requirements.

[0059] S3. Preparation of composite positive electrode materials

[0060] The positive electrode active material, solid electrolyte and conductive carbon black were mixed according to the above design ratio, and the powder was premixed in a vacuum zirconia ball mill with a ball-to-material ratio of 10:1. The premixing was performed at 150rpm for 1h. Polyvinylidene fluoride (PVDF) was used as a binder and TNMP was used as a solvent. The mass ratio of the composite positive electrode material to polyvinylidene fluoride was controlled to be 100:3. Finally, the following three composite positive electrode powders were prepared:

[0061] Li(Ni 0.83 Co 0.11 Mn 0.06 )O2: Li6PS5Cl: Super P=70:24:6;

[0062] Li(Ni 0.6 Co 0.2 Mn 0.2 )O2: Li6PS5Cl: Super P=70:25:5;

[0063] Li(Ni 0.33 Co 0.33 Mn 0.33 )O2: Li6PS5Cl: Super P=70:20:10.

[0064] S4, layer by layer coating

[0065] S4-1, prepare the positive electrode material Li (Ni 0.83 Co 0.11 Mn 0.06 )O2 slurry is coated on the aluminum foil. After the first layer of coating is completed, the electrode is placed in a vacuum drying oven and the temperature is set to 100°C for drying to remove the solvent.

[0066] S4-2, coating the second layer of Li (Ni 0.6 Co 0.2 Mn 0.2 )O2 slurry, and annealing is performed after completing the drying process.

[0067] S4-3, coating the third layer of Li (Ni 0.33 Co 0.33 Mn 0.33 )O2 slurry is also dried and annealed.

[0068] After each layer is coated, a low-temperature annealing at 250° (1 hour) is used to promote the stability of the crystal structure of the positive electrode material and improve the adhesion between the layers to ensure good bonding between the interlayer interfaces. The loading of the three layers is controlled by adjusting the scraper gap, and the final loading is 45 mg / cm 2 The positive electrode.

[0069] S5. Assembly and pressing

[0070] Cut the coated pole pieces into round pieces with a diameter of 10 mm and place them at the bottom of the homemade mold to ensure stable position. Evenly spread 110 mg of Li6PS5Cl solid electrolyte powder, or use Li6PS5Cl electrolyte film to ensure the flatness and uniform distribution of the electrolyte layer. Use slight pressure to compact the electrolyte surface to ensure that it is in full contact with the positive electrode material. Then, spread the graphite composite negative electrode powder (Gr: Li6PS5Cl = 6:4) evenly on the electrolyte surface according to the N / P ratio of 1.3. In order to increase the density of the electrolyte layer and ensure good contact between different layers, an axial pressure of 450 MPa is applied. Finally, the entire battery assembly is placed under a stacking pressure of 60 MPa for pressing to ensure close bonding between the layers of materials. As Figure 1 Shown is a schematic structural diagram of a positive electrode sheet based on a gradient structure and its corresponding solid-state battery.

[0071] After the battery is assembled, it is packaged and subjected to charge and discharge cycle tests, conventional rate performance tests, and total impedance tests.

[0072] Example 2

[0073] This embodiment provides a method for preparing a positive electrode plate based on a gradient structure and a method for preparing a battery using the positive electrode plate. Different from Example 1, in this embodiment: the ratio of the solid electrolyte in the bottom layer is adjusted to positive electrode active material: solid electrolyte: conductive carbon black = 70:22:8, and the ratio of the middle layer (positive electrode active material: solid electrolyte: conductive carbon black = 70:25:5) and the surface layer (positive electrode active material: solid electrolyte: conductive carbon black = 70:20:10) remains unchanged.

[0074] The specific steps are as follows:

[0075] S1. Material selection and gradient design

[0076] The bottom layer is made of high nickel content (Li(Ni 0.83 Co 0.11 Mn 0.06 )O2) cathode material, aiming to increase the energy density of the battery; the intermediate layer uses a cathode material with a moderate nickel content and increased manganese content ((Li(Ni 0.6 Co 0.2 Mn 0.2 )O2) to enhance the structural stability of the battery; the surface layer uses a positive electrode material with a high manganese content (Li(Ni 0.33 Co 0.33 Mn 0.33 )O2), improving cycle life and oxidation resistance. The solid electrolyte uses Li6PS5Cl, which has excellent ionic conductivity and good interface stability, which helps to reduce interface resistance. Conductive carbon black uses Super P, which can effectively enhance the electronic conductivity of the electrode. As a binder, polyvinylidene fluoride (PVDF) is used to ensure a good combination of the positive electrode material and the conductive carbon black. In addition, N,N,N-trimethyl-2-aminoethanol (TNMP) is selected as a solvent to improve the solubility and dispersibility of the slurry and ensure its uniformity.

[0077] S2. Gradient structure design and ratio optimization

[0078] According to the design concept of the gradient structure, the ratio of solid electrolyte and conductive carbon black in each layer of positive electrode material is optimized according to the ionic and electronic conductivity requirements of the battery.

[0079] The bottom layer (close to the current collector) is designed as positive electrode active material: solid electrolyte: conductive carbon black = 70:22:8. The proportion of conductive carbon black is increased to effectively reduce the contact resistance at the interface between the current collector and the coating, improve the internal resistance and cycle stability, and enhance the ionic conductivity by appropriately increasing the proportion of solid electrolyte.

[0080] The middle layer (the side away from the current collector) is designed as positive electrode active material: solid electrolyte: conductive carbon black = 70:25:5. The solid electrolyte ratio is moderate, aiming to balance the conductivity of ions and electrons and support efficient charging and discharging of the battery.

[0081] The surface layer (the side away from the current collector) is designed to be positive electrode active material: solid electrolyte: conductive carbon black = 70:20:10, reducing the proportion of solid electrolyte, significantly increasing the content of conductive carbon black, and optimizing electronic conductivity to meet high load requirements.

[0082] S3. Preparation of composite positive electrode materials

[0083] The positive electrode active material, solid electrolyte and conductive carbon black were mixed according to the above design ratio, and the powder was premixed in a vacuum zirconia ball mill with a ball-to-material ratio of 10:1. The premixing was performed at 150rpm for 1h. Polyvinylidene fluoride (PVDF) was used as a binder and TNMP was used as a solvent. The mass ratio of the composite positive electrode material to polyvinylidene fluoride was controlled to be 100:3. Finally, the following three composite positive electrode powders were prepared:

[0084] Li(Ni 0.83 Co 0.11 Mn 0.06 )O2: Li6PS5Cl: Super P=70:22:8;

[0085] Li(Ni 0.6 Co 0.2 Mn 0.2 )O2: Li6PS5Cl: Super P=70:25:5;

[0086] Li(Ni 0.33 Co 0.33 Mn 0.33 )O2: Li6PS5Cl: Super P=70:20:10.

[0087] S4, layer by layer coating

[0088] S4-1, prepare the positive electrode material Li (Ni 0.83 Co 0.11 Mn 0.06 )O2 slurry is coated on the aluminum foil. After the first layer of coating is completed, the electrode is placed in a vacuum drying oven and the temperature is set to 100°C for drying to remove the solvent.

[0089] S4-2, coating the second layer of Li (Ni 0.6 Co 0.2 Mn 0.2 )O2 slurry, and annealing is performed after completing the drying process.

[0090] S4-3, coating the third layer of Li (Ni 0.33 Co 0.33 Mn 0.33 )O2 slurry is also dried and annealed.

[0091] After each layer is coated, a low-temperature annealing at 250° (1 hour) is used to promote the stability of the crystal structure of the positive electrode material and improve the adhesion between the layers to ensure good bonding between the interlayer interfaces. The loading of the three layers is controlled by adjusting the scraper gap, and the final loading is 45 mg / cm 2 The positive electrode.

[0092] S5. Assembly and pressing

[0093] Cut the coated pole piece into a circular piece with a diameter of 10 mm and place it at the bottom of the homemade mold to ensure stable position. Evenly lay 110 mg of Li6PS5Cl solid electrolyte powder, or use Li6PS5Cl electrolyte film to ensure the flatness and uniform distribution of the electrolyte layer. Use slight pressure to compact the electrolyte surface to ensure that it is in full contact with the positive electrode material. Then, the graphite composite negative electrode powder (Gr: Li6PS5Cl = 6:4) is evenly spread on the surface of the electrolyte according to the N / P ratio of 1.3. In order to increase the density of the electrolyte layer and ensure good contact between different layers, an axial pressure of 450 MPa is applied. Finally, the entire battery assembly is pressed under a stacking pressure of 60 MPa to ensure close bonding between the layers of material.

[0094] After the battery is assembled, it is packaged and subjected to charge and discharge cycle tests, conventional rate performance tests, and total impedance tests.

[0095] Example 3

[0096] This embodiment provides a method for preparing a positive electrode plate based on a gradient structure and a method for preparing a battery using the positive electrode plate. Different from Example 1, in this embodiment: the surface layer is positive electrode active material: solid electrolyte: conductive carbon black = 70:24:6, and the bottom layer and the middle layer remain unchanged (positive electrode active material: solid electrolyte: conductive carbon black = 70:25:5 and 70:22:8 respectively).

[0097] The specific steps are as follows:

[0098] S1. Material selection and gradient design

[0099] The bottom layer is made of high nickel content (Li(Ni 0.83 Co 0.11 Mn 0.06 )O2) cathode material, aiming to increase the energy density of the battery; the intermediate layer uses a cathode material with a moderate nickel content and increased manganese content ((Li(Ni 0.6 Co 0.2 Mn 0.2 )O2) to enhance the structural stability of the battery; the surface layer uses a positive electrode material with a high manganese content (Li(Ni 0.33 Co 0.33 Mn 0.33)O2), improving cycle life and oxidation resistance. The solid electrolyte uses Li6PS5Cl, which has excellent ionic conductivity and good interface stability, which helps to reduce interface resistance. Conductive carbon black uses Super P, which can effectively enhance the electronic conductivity of the electrode. As a binder, polyvinylidene fluoride (PVDF) is used to ensure a good combination of the positive electrode material and the conductive carbon black. In addition, N,N,N-trimethyl-2-aminoethanol (TNMP) is selected as a solvent to improve the solubility and dispersibility of the slurry and ensure its uniformity.

[0100] S2. Gradient structure design and ratio optimization

[0101] According to the design concept of the gradient structure, the ratio of solid electrolyte and conductive carbon black in each layer of positive electrode material is optimized according to the ionic and electronic conductivity requirements of the battery.

[0102] The bottom layer (close to the current collector) is designed as positive electrode active material: solid electrolyte: conductive carbon black = 70:24:6. The proportion of conductive carbon black is increased to effectively reduce the contact resistance at the interface between the current collector and the coating, improve the internal resistance and cycle stability, and enhance the ionic conductivity by appropriately increasing the proportion of solid electrolyte.

[0103] The middle layer (the side away from the current collector) is designed as positive electrode active material: solid electrolyte: conductive carbon black = 70:25:5. The solid electrolyte ratio is moderate, aiming to balance the conductivity of ions and electrons and support efficient charging and discharging of the battery.

[0104] The surface layer (the side away from the current collector) is designed to be positive electrode active material: solid electrolyte: conductive carbon black = 70:22:8, reducing the proportion of solid electrolyte, significantly increasing the content of conductive carbon black, and optimizing electronic conductivity to meet high load requirements.

[0105] S3. Preparation of composite positive electrode materials

[0106] The positive electrode active material, solid electrolyte and conductive carbon black were mixed according to the above design ratio, and the powder was premixed in a vacuum zirconia ball mill with a ball-to-material ratio of 10:1. The premixing was performed at 150rpm for 1h. Polyvinylidene fluoride (PVDF) was used as a binder and TNMP was used as a solvent. The mass ratio of the composite positive electrode material to polyvinylidene fluoride was controlled to be 100:3. Finally, the following three composite positive electrode powders were prepared:

[0107] Li(Ni 0.83 Co 0.11 Mn 0.06 )O2: Li6PS5Cl: Super P=70:24:6;

[0108] Li(Ni 0.6 Co 0.2 Mn0.2 )O2: Li6PS5Cl: Super P=70:25:5;

[0109] Li(Ni 0.33 Co 0.33 Mn 0.33 )O2: Li6PS5Cl: Super P=70:22:8.

[0110] S4, layer by layer coating

[0111] S4-1, prepare the positive electrode material Li (Ni 0.83 Co 0.11 Mn 0.06 )O2 slurry is coated on the aluminum foil. After the first layer of coating is completed, the electrode is placed in a vacuum drying oven and the temperature is set to 100°C for drying to remove the solvent.

[0112] S4-2, coating the second layer of Li (Ni 0.6 Co 0.2 Mn 0.2 )O2 slurry, and annealing is performed after completing the drying process.

[0113] S4-3, coating the third layer of Li (Ni 0.33 Co 0.33 Mn 0.33 )O2 slurry is also dried and annealed.

[0114] After each layer is coated, a low-temperature annealing at 250° (1 hour) is used to promote the stability of the crystal structure of the positive electrode material and improve the adhesion between the layers to ensure good bonding between the interlayer interfaces. The loading of the three layers is controlled by adjusting the scraper gap, and the final loading is 45 mg / cm 2 The positive electrode.

[0115] S5. Assembly and pressing

[0116] Cut the coated pole piece into a circular piece with a diameter of 10 mm and place it at the bottom of the homemade mold to ensure stable position. Evenly lay 110 mg of Li6PS5Cl solid electrolyte powder, or use Li6PS5Cl electrolyte film to ensure the flatness and uniform distribution of the electrolyte layer. Use slight pressure to compact the electrolyte surface to ensure that it is in full contact with the positive electrode material. Then, the graphite composite negative electrode powder (Gr: Li6PS5Cl = 6:4) is evenly spread on the surface of the electrolyte according to the N / P ratio of 1.3. In order to increase the density of the electrolyte layer and ensure good contact between different layers, an axial pressure of 450 MPa is applied. Finally, the entire battery assembly is pressed under a stacking pressure of 60 MPa to ensure close bonding between the layers of material.

[0117] After the battery is assembled, it is packaged and subjected to charge and discharge cycle tests, conventional rate performance tests, and total impedance tests.

[0118] Comparative Example 1

[0119] This comparative example provides a method for preparing a positive electrode plate and a method for preparing a battery using the positive electrode plate. Different from Example 1, this comparative example adopts standard positive electrode materials and proportion design, the ratio of the solid electrolyte in the bottom layer is positive electrode active material: solid electrolyte: conductive carbon black = 70:25:5, and the ratio of all layers is consistent, and the ratio of the middle layer and the surface layer is not specifically optimized.

[0120] The specific steps are as follows:

[0121] S1. Material selection and gradient design

[0122] The bottom layer is made of high nickel content (Li(Ni 0.83 Co 0.11 Mn 0.06 )O2) cathode material, aiming to increase the energy density of the battery; the intermediate layer uses a cathode material with a moderate nickel content and increased manganese content ((Li(Ni 0.6 Co 0.2 Mn 0.2 )O2) to enhance the structural stability of the battery; the surface layer uses a positive electrode material with a high manganese content (Li(Ni 0.33 Co 0.33 Mn 0.33 )O2), improving cycle life and oxidation resistance. The solid electrolyte uses Li6PS5Cl, which has excellent ionic conductivity and good interface stability, which helps to reduce interface resistance. Conductive carbon black uses Super P, which can effectively enhance the electronic conductivity of the electrode. As a binder, polyvinylidene fluoride (PVDF) is used to ensure a good combination of the positive electrode material and the conductive carbon black. In addition, N,N,N-trimethyl-2-aminoethanol (TNMP) is selected as a solvent to improve the solubility and dispersibility of the slurry and ensure its uniformity.

[0123] S2. Gradient structure design and ratio optimization

[0124] According to the design concept of the gradient structure, the ratio of solid electrolyte and conductive carbon black in each layer of positive electrode material is optimized according to the ionic and electronic conductivity requirements of the battery.

[0125] The bottom layer (close to the current collector) is designed as positive electrode active material: solid electrolyte: conductive carbon black = 70:25:5. The proportion of conductive carbon black is increased to effectively reduce the contact resistance at the interface between the current collector and the coating, improve the internal resistance and cycle stability, and enhance the ionic conductivity by appropriately increasing the proportion of solid electrolyte.

[0126] The middle layer (the side away from the current collector) is designed as positive electrode active material: solid electrolyte: conductive carbon black = 70:25:5. The solid electrolyte ratio is moderate, aiming to balance the conductivity of ions and electrons and support efficient charging and discharging of the battery.

[0127] The surface layer (the side away from the current collector) is designed to be positive electrode active material: solid electrolyte: conductive carbon black = 70:25:5, reducing the proportion of solid electrolyte, significantly increasing the content of conductive carbon black, and optimizing electronic conductivity to meet high load requirements.

[0128] S3. Preparation of composite positive electrode materials

[0129] The positive electrode active material, solid electrolyte and conductive carbon black were mixed according to the above design ratio, and the powder was premixed in a vacuum zirconia ball mill with a ball-to-material ratio of 10:1. The premixing was performed at 150rpm for 1h. Polyvinylidene fluoride (PVDF) was used as a binder and TNMP was used as a solvent. The mass ratio of the composite positive electrode material to polyvinylidene fluoride was controlled to be 100:3. Finally, the following three composite positive electrode powders were prepared:

[0130] Li(Ni 0.83 Co 0.11 Mn 0.06 )O2: Li6PS5Cl: Super P=70:25:5;

[0131] Li(Ni 0.6 Co 0.2 Mn 0.2 )O2: Li6PS5Cl: Super P=70:25:5;

[0132] Li(Ni 0.33 Co 0.33 Mn 0.33 )O2: Li6PS5Cl: Super P=70:25:5.

[0133] S4, layer by layer coating

[0134] S4-1, prepare the positive electrode material Li (Ni 0.83 Co 0.11 Mn 0.06 )O2 slurry is coated on the aluminum foil. After the first layer of coating is completed, the electrode is placed in a vacuum drying oven and the temperature is set to 100°C for drying to remove the solvent.

[0135] S4-2, coating the second layer of Li (Ni 0.6 Co 0.2 Mn 0.2 )O2 slurry, and annealing is performed after completing the drying process.

[0136] S4-3, coating the third layer of Li (Ni 0.33 Co 0.33 Mn 0.33 )O2 slurry is also dried and annealed.

[0137] After each layer is coated, a low-temperature annealing at 250° (1 hour) is used to promote the stability of the crystal structure of the positive electrode material and improve the adhesion between the layers to ensure good bonding between the interlayer interfaces. The loading of the three layers is controlled by adjusting the scraper gap, and the final loading is 45 mg / cm 2 The positive electrode.

[0138] S5. Assembly and pressing

[0139] Cut the coated pole piece into a circular piece with a diameter of 10 mm and place it at the bottom of the homemade mold to ensure stable position. Evenly lay 110 mg of Li6PS5Cl solid electrolyte powder, or use Li6PS5Cl electrolyte film to ensure the flatness and uniform distribution of the electrolyte layer. Use slight pressure to compact the electrolyte surface to ensure that it is in full contact with the positive electrode material. Then, the graphite composite negative electrode powder (Gr: Li6PS5Cl = 6:4) is evenly spread on the surface of the electrolyte according to the N / P ratio of 1.3. In order to increase the density of the electrolyte layer and ensure good contact between different layers, an axial pressure of 450 MPa is applied. Finally, the entire battery assembly is pressed under a stacking pressure of 60 MPa to ensure close bonding between the layers of material.

[0140] After the battery is assembled, it is packaged and subjected to charge and discharge cycle tests, conventional rate performance tests, and total impedance tests.

[0141] Comparative Example 2

[0142] This comparative example provides a method for preparing a positive electrode sheet and a method for preparing a battery using the positive electrode sheet. Different from Example 1, the positive electrode active material of this comparative example only contains Li(Ni 0.83 Co 0.11 Mn 0.06 )O2 layer, in which positive electrode active material: solid electrolyte: conductive carbon black = 70:25:5.

[0143] The specific steps are as follows:

[0144] S1. Material selection

[0145] High nickel content (Li(Ni 0.83 Co 0.11 Mn 0.06)O2) is used as the positive electrode material. Li6PS5Cl is used as the solid electrolyte. Super P is used as the conductive carbon black. Polyvinylidene fluoride (PVDF) is used as the binder, and N,N,N-trimethyl-2-aminoethanol (TNMP) is used as the solvent.

[0146] S2. Proportional design

[0147] Positive electrode active material: solid electrolyte: conductive carbon black = 70:25:5.

[0148] S3. Preparation of positive electrode materials

[0149] The positive electrode active material, solid electrolyte and conductive carbon black were mixed according to the above design ratio, and the powder was premixed in a vacuum zirconia ball mill with a ball-to-material ratio of 10:1. The premixing was performed at 150rpm for 1h. Polyvinylidene fluoride (PVDF) was used as a binder and TNMP was used as a solvent. The mass ratio of the composite positive electrode material to polyvinylidene fluoride was controlled to be 100:3. Finally, the composite positive electrode powder was prepared:

[0150] Li(Ni 0.83 Co 0.11 Mn 0.06 )O2: Li6PS5Cl: Super P=70:25:5.

[0151] S4, coating

[0152] The prepared positive electrode material Li(Ni 0.83 Co 0.11 Mn 0.06 )O2 slurry is coated on the aluminum foil. After coating, the electrode is placed in a vacuum drying oven and the temperature is set to 100°C for drying to remove the solvent.

[0153] After coating, low-temperature annealing at 250°C (1 hour) was used to promote the stability of the crystal structure of the positive electrode material and improve the adhesion between the layers to ensure good bonding between the interlayer interfaces. The loading amount was controlled by adjusting the scraper gap, and the final loading amount was 45 mg / cm 2 The positive electrode.

[0154] S5. Assembly and pressing

[0155] Cut the coated pole piece into a circular piece with a diameter of 10 mm and place it at the bottom of the homemade mold to ensure stable position. Evenly lay 110 mg of Li6PS5Cl solid electrolyte powder, or use Li6PS5Cl electrolyte film to ensure the flatness and uniform distribution of the electrolyte layer. Use slight pressure to compact the electrolyte surface to ensure that it is in full contact with the positive electrode material. Then, the graphite composite negative electrode powder (Gr: Li6PS5Cl = 6:4) is evenly spread on the surface of the electrolyte according to the N / P ratio of 1.3. To increase the density of the electrolyte layer, an axial pressure of 450 MPa is applied. Finally, the entire battery assembly is pressed under a stacking pressure of 60 MPa to ensure close bonding between the layers of material.

[0156] After the battery is assembled, it is packaged and subjected to charge and discharge cycle tests, conventional rate performance tests, and total impedance tests.

[0157] The electrochemical performance of the batteries prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was tested, and the test results are shown in Table 1.

[0158] Table 1 Electrochemical performance test results of Examples 1 to 3 and Comparative Examples 1 to 2

[0159]

[0160] According to the test data in the table, it can be seen that compared with Example 1, the proportion of the bottom conductive carbon black in Example 2 is higher, so the electron transmission between the coating and the current collector is enhanced, revealing the importance of the interface between the coating and the current collector. Increasing the amount of the bottom conductive agent can reduce the contact resistance of the interface and improve the internal resistance and cycle performance of the battery. The established optimized gradient structure can reduce the polarization inside the positive electrode plate and reduce the charge carrier transmission barrier in the transmission direction; compared with Example 3, the solid electrolyte in the surface layer of Example 1 is reduced and the conductive carbon black is increased. Such changes are in line with the requirements of ionic and electronic conductivity that vary with thickness, so the overall performance is improved; Comparative Example 1 is a completely homogenized positive electrode material: solid electrolyte: conductive carbon black ratio, and there is no change in the requirements for ionic and electronic conductivity relative to Examples 1-3, so the performance is poor; Comparative Example 2 does not use a three-layer structure and a ratio change, and the overall performance is reduced, proving that the positive electrode plate prepared by the technical solution of the present application can effectively balance multiple performance requirements of the battery under high load conditions, improve the comprehensive performance of the solid-state battery, and provide a feasible technical path for high energy density and long life solid-state lithium batteries.

[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that it is still possible to modify the technical solutions described in the aforementioned embodiments, or to replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A positive electrode sheet based on a gradient structure, characterized in that: It includes a bottom layer, an intermediate layer and a surface layer; the bottom layer, the intermediate layer and the surface layer all include positive electrode active materials prepared by using transition metal materials in different proportions; the transition metal materials include Ni, Co and Mn; from the bottom layer to the surface layer, the Ni content gradually decreases, and the Mn and Co contents gradually increase.

2. The positive electrode sheet based on the gradient structure according to claim 1, characterized in that: The positive electrode active material of the bottom layer includes Li(Ni 0.83 Co 0.11 Mn 0.06 )O2; the positive electrode active material of the intermediate layer includes Li(Ni 0.6 Co 0.2 Mn 0.2 )O2; the positive electrode active material of the surface layer includes Li(Ni 0.33 Co 0.33 Mn 0.33 )O2.

3. The positive electrode sheet based on the gradient structure according to claim 1, characterized in that: The raw material components for preparing the positive electrode plate also include solid electrolyte, conductive carbon black, binder and solvent.

4. The positive electrode sheet based on the gradient structure according to claim 3, characterized in that: The solid electrolyte includes Li6PS5Cl.

5. The positive electrode sheet based on the gradient structure according to claim 3, characterized in that: The conductive carbon black includes Super P conductive carbon black.

6. The positive electrode sheet based on the gradient structure according to claim 3, characterized in that: The binder includes polyvinylidene fluoride.

7. The positive electrode sheet based on the gradient structure according to claim 3, characterized in that: The solvent includes N,N,N-trimethyl-2-aminoethanol.

8. The positive electrode sheet based on the gradient structure according to claim 3, characterized in that: In terms of mass ratio, in the bottom layer, the positive electrode active material: solid electrolyte: conductive carbon black = 70: (20-24): (6-10); in the middle layer, the positive electrode active material: solid electrolyte: conductive carbon black = 70: (24-26): (4-6); in the surface layer, the positive electrode active material: solid electrolyte: conductive carbon black = 70: (18-22): (8-12).

9. A method for preparing a positive electrode sheet according to any one of claims 1 to 8, characterized in that: The following steps are involved: Preparation of composite positive electrode material: mixing positive electrode active material, solid electrolyte and conductive carbon black in proportion, then adding binder and solvent to the composite positive electrode powder, and premixing in a vacuum zirconia ball mill; Layer by layer coating: The first coating layer is to coat the slurry of the bottom cathode material on the aluminum foil; The second layer is coated by coating the slurry of the intermediate layer positive electrode material on the surface of the first layer; The third layer coating is to coat the slurry of the surface positive electrode material on the surface of the second layer; Each layer is dried after coating and heat treated by low temperature annealing.

10. The method for preparing a positive electrode sheet according to claim 9, characterized in that: The load capacity of the three layers is the same.

11. A method for preparing a positive electrode sheet according to claim 10, characterized in that: The total loading of the three layers is 45 mg / cm 2 .

12. The method for preparing a positive electrode sheet according to claim 9, characterized in that: The mass ratio of the composite positive electrode powder to the binder is 100:(1-5).

13. A battery, characterized in that: The battery comprises the positive electrode sheet according to any one of claims 1 to 8 or the positive electrode sheet prepared by any one of the preparation methods according to claims 9 to 13.

14. A battery according to claim 13, characterized in that: The method for preparing the battery comprises the following steps: Cut the positive electrode sheet into round pieces and place them at the bottom of the mold; Evenly spread electrolyte powder or electrolyte film on the positive electrode sheet and compact the electrolyte surface; Spreading the graphite composite negative electrode powder evenly on the surface of the electrolyte; The entire battery assembly is placed under a stacking pressure of 50MPa to 80MPa for pressing to ensure that each layer of material is tightly bonded to prepare a battery.

15. An electronic device, characterized in that: A battery comprising the battery of claim 13 or 14.

Citation Information

Patent Citations

  • NCM ternary cathode material with gradient structure for lithium ion battery, manufacturing method and application

    CN108878869A

  • Lithium battery pole piece and preparation method thereof

    CN111477841A

  • Lithium battery positive electrode structure and all-solid-state thin film lithium battery structure

    CN111490247A

  • Lithium ion battery electrode and preparation method thereof and lithium ion battery

    CN112271270A

  • Flexible solid-state battery

    CN112993382A